IMPLEMENTATION OF A CUSTOMER RELATIONSHIP MANAGEMENT SYSTEM TO IMPROVE THE QUALITY OF SERVICES OF SIDODADI EMY OLSHOP STORE - Kiki Andriani; Neni Mulyani; Elly Rahayu (Informatika, Universitas Jenderal Soedirman, 2022)
The development of information technology is currently very rapid by utilizing the internet as one of the factors of business success in conducting online-based fashion service and sales transactions. The sales system at the EMY Olshop store which is located at Jl Ir Sutami Sidodadi, Asahan Regency, North Sumatra 21211 needs to be improved, so that it can compete with other competitors who can provide good and satisfying service to every customer. To create customer satisfaction, EMY Olshop stores must recognize a desire from their customers through efforts to manage good relationships with customers. Customer Relationship Management is a system that can be developed with the aim of supporting the fashion business in order to create a close relationship with its customers, CRM also helps the EMY Olshop store to find out what customers need related to fashion and important information from the store. The results of this study can help the store in promoting fashion outside the region, maintain good relations with customers, get new customers, access the fashion offered by the EMY Olshop store. In addition, there is also a CRM such as discounts, live chat, comments, reviews and selection of address options that will make it easier for the store to sell various types of high-quality fashion according to customer needs and desires.